Peripheral Cemento-ossifying Fibroma - Adhikari, Khushbu; Shah, Anita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Localised gingival overgrowth is commonly encountered in our practice. They can be histologically different such as the peripheral giant cell granuloma, giant cell fibroma, pyogenic granuloma or fibroma. A diagnosis based only on the clinical feature is difficult to make because of their similarity in clinical presentation with other gingival overgrowths. Therefore, histopathological examination is mandatory for making an accurate diagnosis that will ultimately help us to treat the underlying disease. This is a case report of Peripheral cemento-ossifying fibroma, which is a slow progressing and asymptomatic gingival growth until it causes noticeable deformity.